Methodological foundations of soft skills of musical art teachers in pedagogical institutions of higher education - Mozgalova, Nataliia G.; Baranovska, Iryna G.; Hlazunova, Iryna K.; Mikhalishen, Aleksandr V.; Kazmirchuk, Natalia S. (Linguistics and Culture Review, 2021)
Discussions about the exact sciences dominate education these days, with a lot of emphasis on teaching STEM disciplines. Because of this, teachers of other subjects, such as art or history, felt a little left out when talking about how to properly prepare students for future careers. However, there is even less attention is paid to the soft skills that students need to succeed after they graduate and work. The classes designed specifically for soft skills are the rare occurrence, but that does not mean these skills are not important. This determines the relevance of this paper. The purpose of the paper was to highlight the necessary soft skills for future specialists in musical or artistic disciplines, as well as to trace their differences with hard skills. The key research method was the analysis of theoretical materials and the development of general soft skills, which are necessary for the training of teachers of musical art, and the development of which is important for teachers to pay attention to. Teachers will not always have time to plan classes that perfectly combine hard and interpersonal skills.